WAREHOUSE STORAGE OTOMATIS BERBASIS SIEMENS S71200 DAN FACTORY I/O - Al Mahdali; Lutfi; Andi Ichlasul Amal (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
This study aims to develop an automated warehouse storage system using Factory I/O and Siemens S7-1200 PLC. This research was conducted at the Control and Automation Laboratory of the ATI Makassar Polytechnic from July to September 2023. The research method used is quantitative deductive with an experimental approach, including the steps of literature study, system requirements analysis, state diagram design, and system testing through virtual simulation. The algorithm used is a state diagram algorithm consisting of ten states, namely: standby mode, entry to loader, fork left, lift up, fork middle, target position, fork right, lift down, fork middle, and home position. The results of the study showed that the state diagram algorithm was successfully converted into 14 networks (RUNG) in the PLC ladder, consisting of one RUNG for Flowchart (Indicator RUN), ten RUNG for state diagrams, and three RUNG for output devices (Fork Left, Fork Right, and Lift). The automated warehouse storage system successfully automates the process of storing cargo in the form of boxes and pallets from the first rack to the 54th rack automatically. This study shows that the automated warehouse storage system can run according to the planned design and provide significant contributions to the DCS and SCADA practicum at the ATI Makassar Polytechnic.